Analisis Pengelolaan Alokasi Dana Desa dalam Pembangunan Infrastruktur di Desa Pangkoh Sari, Kecamatan Pandih Batu Kabupaten Pulang Pisau - Suratmoko, Bayu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study aims to determine, analyze, and describe the extent to which the management of Village Fund Allocation (ADD) in Pangkoh Sari Village is conducted properly and in accordance with the applicable regulations, while also ensuring that the villagers understand its allocation and use. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation in Pangkoh Sari Village. Data analysis includes procedures for data reduction, data presentation, and drawing conclusions or verification. The findings indicate that the ADD in Pangkoh Sari Village has not been fully utilized for infrastructure development, instead focusing on improving social welfare, community services, and local income. However, one of the main obstacles identified is the lack of community awareness and participation in bureaucratic socialization efforts, leading to uneven development across the village. The study emphasizes the importance of communication and collaboration between the village government and the community to ensure more transparent and targeted use of the ADD. Improving socialization and community participation could help address these obstacles.